KONTRIBUSI KEKUATAN OTOT TUNGKAI DAN KELENTUKAN TUBUH (PUNGGUNG) TERHADAP KETEPATAN SHOOTING PADA PERMAINAN SEPAK BOLA SSB TUNAS INTI SIAK - Sinta Lina; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem from this observation to determine the contribution of leg muscle strength and body flexibility with precision shooting in the game of football SSB Tunas Inti Siak.The population in this research is SSB Tunas Inti Siak soccer totaling 18 people by using the technique of total side where all the population sampled, to obtain research data used leg dynamometer test, body flexibility with Bridge-ups and shooting accuracy. Data were analyzed by simple and multiple product moment.Testing normality of the variables X1, L0maks <Ltable or 0.1112<0.200, X2, L0maks <Ltable or 0.0779<0.200 and testing normality of variables Y, L0maks <Ltable or 0.1388<0.200 summed it all normally distributed, then performed correlation analysis of the data obtained r1 0.484, where rresult> rtable or 0.484 > 0.482, analysis of data obtained r2 of 0.485, which rresult> rtable or 0.485 > 0.482, further analysis of the data obtained correlation R= 0.562 where rresult > rtable or 0.562 > 0.482. Data thus significantly with the level of relationship that is strong enough.Based on the analysis of the data found that the results obtained from leg muscle strength contributes to the accuracy of shooting in the game of football SSB Tunas Inti Siak.From the results obtained have contributed to the flexibility of the body in the accuracy shooting game soccer SSB Tunas Inti Siak. There contributed jointly between leg muscle strength and body flexibility as to the accuracy of Shooting in the game of football SSB Tunas Inti Siak.Keywords: Limb Muscle Strength, flexibility Body, Accuracy Shooting